Efeitos de transferência do estudo musical sobre o desenvolvimento da linguagem na primeira infância - Soares , Neuriane da Silva Pereira (2022)
This article aims to investigate the effects of transferring musical learning to oral and written language in early childhood. It presents information for parents and teachers about musical learning and whether it can be related to language development, problematizing a common sense issue that has not yet been analyzed in works in Portuguese. This study was developed in a systematic literature review format. Studies that focused on early childhood were verified and we identified that part of them proved the existence of transference effects of musical study related to language development, others considered the results as a quasi-transfer effect, as there were no significant improvements in all tests performed and , finally, studies that did not prove the effects of transference, opening the possibility for the existence of other factors that interfere in the process of linguistic development in early childhood.